Practices and preferences in the use of magnification among endodontists and restorative dentists: A multicentre study. - Azhar Iqbal; Mohmed Isaqali Karobari; Deepti Shrivastava; Kumar Chandan Srivastava; Bilal Arjumand; Hmoud Ali Algarni; Meshal Aber Alonazi; Muhsen Alnasser; Osama Khattak; Jamaluddin Syed; Reham Mohmad Attia; Asma Abubakar Rashed; et al. (PLoS ONE)
Background and objectives Aim of the current study was to assess the perception, preference, and practice of endodontists and restorative dentists at different locations around the world about dental magnification instruments. Materials and methods A multicenter, cross-sectional study was ethically approved from the local committee of bioethics. After thorough literature search, a questionnaire was designed and validated. Later, the questionnaire was distributed to 10% (53 participants) of the total planned participants to conduct a pilot study. Based on the feedback from these participants, any ambiguities or discrepancies observed in the items and content of the questionnaire was modified. The questionnaire was assessed for its internal consistency as part of validating the items with Cronbach's alpha of 0.80. The completed questionnaire with an informed consent form for the participant was administered to the endodontists and restorative dentists in three different geographical regions namely MENA (Middle East and Northern Africa), British-Isles, and Indian Sub-continent using WhatsApp through the snowball convenience sampling technique. Results Majority of the participants were male (56.5%) and in the age group of 25-35 years (30.3%). About 68.9% were from Indian sub-continent, followed by the British-Isles (16.5%) and the least (14.6%) were from the MENA region. By large, the participants of the present study, strongly agreed that dental magnification devices improved ergonomics, quality of work, and should be considered as standard of care in modern endodontic. Flip-up magnifiers (51.1%) and medium (8x-16x) magnification were preferred by majority of the participants. About 46.3% of specialist reported that they always used devices for all operative and endodontic procedures, especially while locating hidden and canals and negotiating calcified canals. Participants practicing in British-Isles have 2.42 times (P<0.05) higher adequate perception with reference participants in Indian sub-continent. Additionally, participants with fellowship have 2.77 times more (P<0.01) adequate perception with reference to their counterparts with a master's degree. Conclusions Most of the participants believe that dental magnification devices enhance the prognosis and quality of treatment of possibly all operative and endodontics procedures. Thus, emphasized on the inclusion of devices in the postgraduate curriculum and signifies the role of continuing dental education for specialist and dental assistant handling devices. However, multicenter studies with larger sample is required for generalizing the results.